Successful Treatment of Brain Abscess Caused by Nocardia farcinica with Combination Therapy Despite Discrepancies in In Vitro Results: A Case Report and Review of Diagnostic and Therapeutic Challenges - Eva Larrañaga Lapique; Salomé Gallemaers; Sophie Schuind; Chiara Mabiglia; Nicolas Yin; Delphine Martiny; Maya Hites (Microorganisms, 2025)
Nocardia spp. is an environmental Gram-positive bacterium able to cause infections in humans, predominantly of an opportunistic nature. Nocardial brain abscesses are rare and result from dissemination from another primary lesion, mainly observed in immunocompromised hosts. The diagnosis of nocardiosis relies on direct examination and bacterial culture, but antimicrobial susceptibility testing (AST) remains controversial due to technical challenges, limited standardization, and a paucity of studies correlating in vitro susceptibility with clinical efficacy. Management is challenging and usually based on expert opinion, as robust evidence is limited. In this case report, we describe an immunocompromised patient with a Nocardia farcinica brain abscess who achieved clinical resolution following combination therapy that included ceftriaxone, despite in vitro resistance, illustrating the complexities in interpreting AST and guiding treatment decisions in rare infections.